Impact of continuous glucose monitoring on diabetes management and marital relationships of adults with Type 1 diabetes and their spouses: a qualitative study. Issue 1 (24th July 2013) - Ritholz, M. D.; Beste, M.; Edwards, S. S.; Beverly, E. A.; Atakov‐Castillo, A.; Wolpert, H. A.
Abstract Aims To examine the impact of continuous glucose monitoring on diabetes management and marital relationships of adults with Type 1 diabetes and their spouses. Methods Nine younger (30–49 years) and 11 older (50–70 years) patients with Type 1 diabetes and 14 spouses participated in eight focus groups specific to age and role (patient or spouse). Audio‐recorded data were transcribed, coded and analysed using thematic analysis and aided by NVivo software. Results Qualitative analysis revealed participants perceived continuous glucose monitoring as positively influencing hypoglycaemia management by decreasing spouses' anxiety, vigilance and negative experiences. Participants also described continuous glucose monitoring as promoting collaborative diabetes management and increasing spousal understanding of diabetes, especially when planning and managing pregnancy. Couples' conflicts occurred when (1) patients assumed sole responsibility for continuous glucose monitoring and/or did not respond to night‐time glucose alarms and (2) spouses did not understand alarms and felt frustrated and helpless to assist patients. Conclusions Our findings suggest that continuous glucose monitoring may positively impact collaborative diabetes management and marital relationships of patients with Type 1 diabetes and their spouses. However, reluctance to collaborate and lack of understanding may contribute to couples' conflicts around continuous glucose monitoring. Our findings have important implications for clinical care and point to the need for interventions that include spouses in continuous glucose monitoring training to increase their understanding of continuous glucose monitoring, minimize risk for spousal conflict and enhance collaborative diabetes management. Further studies are needed to explore these issues in more detail and depth with larger and more diverse populations.